An acquired Bartter syndrome with secondary Sjögren syndrome - Naik, Manjiri R.; Patel, Shubham M.; Maindarkar, Parth G.; Khade, Shamisha S. (International Journal of Research in Medical Sciences, 2023)
Renal tubular involvement in Sjögren’s syndrome (SS) often described with renal tubular acidosis, nephrogenic diabetes insipidus, or rarely with Fanconi syndrome. SS presenting with clinical features of Bartter’s syndrome or Gitelman’s syndrome is rare. We report a case of a female patient who presented an acquired Bartter syndrome with a secondary SS. Our case highlights the fact that hypokalemia with metabolic alkalosis in an adult patient should prompt clinicians to look for common and uncommon conditions. While assessing for abnormal conditions, acquired Bartter syndrome should be considered if a patient has an underlying autoimmune, endocrine, or connective tissue disease.